Validation and cross‐cultural adaptation of the Arabic version of the self‐reported mini olfactory questionnaire (Self‐MOQ) - Rayan Alfallaj; Hisham Almousa; Nawaf Alsubaie; Yara Akkielah; Tamer A. Mesallam; Ibrahim Sumaily; Saad Alsaleh (Laryngoscope Investigative Otolaryngology, 2023)
Abstract Background A simple self‐assessment screening questionnaire for olfactory dysfunction is direly needed in Rhinology practice, and this questionnaire should be accessible to affected individuals. The self‐reported mini olfactory questionnaire (Self‐MOQ), constructed to fill this gap, could be an important tool, especially in the era of telemedicine. Objectives The aim of this study was to assess the validity and reliability of the Arabic version of the self‐reported mini olfactory questionnaire (Self‐MOQ) in patients with olfactory dysfunction. Methodology This cross‐sectional study included all adult patients who visited a rhinology clinic between January and June 2023 with a complaint of olfactory dysfunction and a control group. The participants completed a questionnaire that included items on demographics, risk factors of olfactory dysfunction, the olfaction VAS, SNOT‐22, and Arabic Self‐MOQ. The Self‐MOQ was forward‐ and back‐translated by qualified professional translators familiar with American English and Arabic. The reliability of the Arabic Self‐MOQ was evaluated using Cronbach's α. The test–retest reliability was assessed by estimating the intraclass correlation coefficient (ICC) for the total Arabic Self‐MOQ score and the individual items. The discriminative ability was examined by comparing the scores of the case and control groups. The construct validity was assessed by comparing the Arabic Self‐MOQ to the olfaction VAS. Results The study sample included 307 respondents (196 cases and 111 controls; 34 undertook the retest). The Cronbach's α coefficients were 0.92 (total Self‐MOQ) and considered excellent. The ICC for the total Self‐MOQ score was 0.87 (95% CI: 0.757, 0.933; p < .001), which indicated good test–retest reliability. Strong correlations were observed between the Self‐MOQ items and VAS scores (r = 0.732, p < .001), (r = 0.689, p < .001). Conclusion The current investigation showed the Arabic version of the Self‐MOQ to be a reliable tool for olfactory dysfunction screening.